2003
DOI: 10.1038/sj.bmt.1704173
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thalidomide on stem cell collection and engraftment in patients with multiple myeloma

Abstract: Summary:The purpose of this study was to determine the effect of thalidomide on stem cell collection and engraftment in patients with multiple myeloma. We performed a retrospective review of 67 patients newly diagnosed with multiple myeloma at Mayo Clinic and treated with a single regimen prior to stem cell transplantation between January of 2000 and September of 2001. Stem cells were collected from 24 patients who received thalidomide, 200 mg/day, with dexamethasone as initial therapy before stem cell collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
24
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 29 publications
5
24
0
Order By: Relevance
“…It has been confirmed by many study groups that THAL as a single agent (Dmoszynska et al, 2000;Patriarca et al, 2003) or combined with VAD (Ahmad et al, 2002;Pitini et al, 2003) could be a suitable bridging regimen to PBSC collection and autologous SCT for VAD-refractory MM patients. Moreover, Ghobrial et al (2003) showed that THAL does not substantionally affect peripheral blood mobilisation or engraftment, which is in line with our observation. For patients with low pretreatment level, other therapeutical options, such as a combination of THAL with chemotherapy or bortezomid, should be considered since such options can significantly increase the response rate.…”
Section: Discussionsupporting
confidence: 92%
“…It has been confirmed by many study groups that THAL as a single agent (Dmoszynska et al, 2000;Patriarca et al, 2003) or combined with VAD (Ahmad et al, 2002;Pitini et al, 2003) could be a suitable bridging regimen to PBSC collection and autologous SCT for VAD-refractory MM patients. Moreover, Ghobrial et al (2003) showed that THAL does not substantionally affect peripheral blood mobilisation or engraftment, which is in line with our observation. For patients with low pretreatment level, other therapeutical options, such as a combination of THAL with chemotherapy or bortezomid, should be considered since such options can significantly increase the response rate.…”
Section: Discussionsupporting
confidence: 92%
“…[28][29][30] In a recent study, 31 early platelet engraftment of 20 000/ml was affected by previous thalidomide use. In line with other studies, we found on univariate analysis that the platelet engraftment (420 000/ml) was affected by the number of CD34 cells infused.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the impact of the initial treatment on engraftment post ASCT, controversial results have been published. 2,3 In our study, a delayed engraftment in patients previously treated with Thal-Dex was observed.…”
mentioning
confidence: 77%